Psychological assistance to a neurological patient. Practical experience during the war - Dragomanova Тетяна (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online. In the article, the author emphasizes the role of psychological intervention in the treatment of neurological patients. He notes that the psychologist helps the doctor to implement an individual approach to the patient by assessing his mental state, features of the course of the disease. In addition, the advantage of the psychologist’s actions in the modern clinic is the joint, coordinated actions of the interdisciplinary team during the treatment and rehabilitation of the patient, which contribute to the most complete recovery. The article focuses on the fact that military actions and psycho-traumatic consequences of the war undoubtedly only contributed to the spread of neurological, in particular, vascular diseases. There are studies that prove a direct link between stress and hypertension, between stress and cardiovascular diseases, which are the main causes of neurological diseases. The attention of the author of the article was focused on helping patients with cerebrovascular diseases, as they make up the largest part of neurological patients (about 60%). And psychological help after a stroke is provided by the National Program of Medical Guarantees.